2017
DOI: 10.1038/s41598-017-05364-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association Landscape of Myelin Basic Protein Portrays Formation of the Myelin Major Dense Line

Abstract: Compact myelin comprises most of the dry weight of myelin, and its insulative nature is the basis for saltatory conduction of nerve impulses. The major dense line (MDL) is a 3-nm compartment between two cytoplasmic leaflets of stacked myelin membranes, mostly occupied by a myelin basic protein (MBP) phase. MBP is an abundant myelin protein involved in demyelinating diseases, such as multiple sclerosis. The association of MBP with lipid membranes has been studied for decades, but the MBP-driven formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
171
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(195 citation statements)
references
References 92 publications
23
171
1
Order By: Relevance
“…Similarly to MBP and P2 (Raasakka et al 2017; Ruskamo et al 2014), P0ct is capable of inducing concentration-dependent solution turbidification, when mixed with lipid vesicles of net negative charge (Raasakka et al 2019b). The turbidity can arise from vesicle fusion and/or aggregation, and different processes may be dominant in different samples with respect to the measured signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to MBP and P2 (Raasakka et al 2017; Ruskamo et al 2014), P0ct is capable of inducing concentration-dependent solution turbidification, when mixed with lipid vesicles of net negative charge (Raasakka et al 2019b). The turbidity can arise from vesicle fusion and/or aggregation, and different processes may be dominant in different samples with respect to the measured signal.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the small size of P0ct and the nature of the disease mutations in it, many of which change its electrostatic charge, impairment in the function of P0ct as a membrane binding/stabilizing segment is a possible functional mechanism. We used methodologies established earlier for myelin basic protein (MBP) (Raasakka et al 2017) and wild-type P0ct (wt-P0ct) (Raasakka et al 2019a; Raasakka et al 2019b) to characterize structure-function relationships of the CMT- and DSS-related P0ct variants. Our results suggest that D224Y is a hypermyelinating gain-of-function mutation, which is in line with the clinically relevant phenotype of abnormally thickened myelin sheaths (Fabrizi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MBP has a high content of positively charged residues and, therefore, binds to the negatively charged lipids of the cytoplasmic leaflets of the bilayer via electrostatic interaction. Moreover, by its association to the inner leaflet of the membrane bilayer, hydrophobic interactions take over and MBP undergoes a phase transition into a cohesive mesh‐like protein network (Aggarwal et al, ; Raasakka et al, ). Using AFM, it was found that MBP adsorbs to myelin bilayer surfaces in a cooperative fashion, involving close protein–protein and protein–lipid/lipid domain interactions, suggesting that MBP contributes to myelin stability through strong adhesion forces (Lee et al, ).…”
Section: Oligodendrocyte Mechanosensing For Myelinationmentioning
confidence: 99%
“…65 In this process, MBP neutralizes the membrane and pulls the inner leaflets of myelin sheaths close to each other, forming the major dense line (MDL). 69,70 The extracellular compaction, on the other hand, is a process where the outer surfaces of myelin membranes are brought together, creating intraperiod line (IPL). 71 Compared to intracellular compaction, extracellular compaction is relatively less well understood.…”
Section: Myelinationmentioning
confidence: 99%